2020
DOI: 10.3390/nano10122557
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Gold Nanohole Arrays for Surface-Enhanced Sum Frequency Generation Detection

Abstract: Nobel metal nanohole arrays have been used extensively in chemical and biological systems because of their fascinating optical properties. Gold nanohole arrays (Au NHAs) were prepared as surface plasmon polariton (SPP) generators for the surface-enhanced sum-frequency generation (SFG) detection of 4-Mercaptobenzonitrile (4-MBN). The angle-resolved reflectance spectra revealed that the Au NHAs have three angle-dependent SPP modes and two non-dispersive localized surface plasmon resonance (LSPR) modes under diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…For example, Humbert et al found that the SFG signals of thiophenols grafted on gold nanospheres can be detected even if the surface coverage of thiophenol molecules is as low as 1%. , Wang et al significantly enhanced the monolayer SFG signals of p -mercaptobenzonitrile adsorbed on Au films by using shell-isolated nanoparticles as nanoantennas and found that the nonlinear coupling of SFG and DFG contributed to signal enhancement . The enhancement factor is reported to range from 10 to 10 5 . ,,, However, a few very limited works have been reported to address the influence of plasmon local electric field on the enhancements in SFG intensity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Humbert et al found that the SFG signals of thiophenols grafted on gold nanospheres can be detected even if the surface coverage of thiophenol molecules is as low as 1%. , Wang et al significantly enhanced the monolayer SFG signals of p -mercaptobenzonitrile adsorbed on Au films by using shell-isolated nanoparticles as nanoantennas and found that the nonlinear coupling of SFG and DFG contributed to signal enhancement . The enhancement factor is reported to range from 10 to 10 5 . ,,, However, a few very limited works have been reported to address the influence of plasmon local electric field on the enhancements in SFG intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, metasurfaces can display a virtually unlimited variety of shapes and compositions (Figure 2), including nanoholes, [36][37][38] nanoparticles, [39][40][41] pillars, [42,43] chiral shapes, [44][45][46][47][48] and antennas, [49][50][51][52] translating directly into an incredible versatility of their optical response, which can be tuned by modifying both the localized plasmonic response of each repeating unit, as well as the geometrical parameters of the array. These parameters will ultimately regulate the quality and the spectral position of all localized and collective resonances, driving the boost of quantum efficiency of the various NL optical processes.…”
Section: Plasmonic Metasurfaces and Non-linear Opticsmentioning
confidence: 99%
“…This is advantageous because SFG signals can be weak depending on the order and symmetry of adsorbed molecules at the interface. , Therefore, plasmonic surface enhancement of signals, in analogy to surface-enhanced Raman spectroscopy, has been employed to increase achiral SFG signal levels. Plasmonic resonances can be excited in nanostructured materials, with concomitant amplification of electromagnetic fields at subwavelength particle dimensions. Metal structures with plasmonic resonances overlapping with the fundamental or signal beams can lead to significant signal enhancement. For this reason, the SFG response of metal nanoparticles with different sizes and shapes has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%